2008
DOI: 10.1136/bjo.2008.149203
|View full text |Cite
|
Sign up to set email alerts
|

Provision and cost of children's and young people's eye services in the UK: findings from a single primary care trust

Abstract: Although the prevalence of significant visual impairment is low in childhood, overall, eye conditions are common in children and may have lifelong implications. The resources required to provide a comprehensive paediatric eye service, to screen for and manage common eye conditions, and support those with serious eye conditions or visual impairment, are significant. This study aids quantified prediction of future service usage, and facilitates decision-making on resource allocation and workforce organisation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…The share of inpatient care expenditure relative to total health-care expenditure among children with difficulty in vision was not as high as that among children with disabilities in other domains. This low share of inpatient care is consistent with the fact that among the pediatric population in the UK, the proportion of children who received hospital eye services and required hospital admission was low (less than 10%) and with the fact that the total cost of ophthalmic surgery and inpatient eye services was less than that of ophthalmology outpatient eye services 15 ) .…”
Section: Discussionsupporting
confidence: 71%
“…The share of inpatient care expenditure relative to total health-care expenditure among children with difficulty in vision was not as high as that among children with disabilities in other domains. This low share of inpatient care is consistent with the fact that among the pediatric population in the UK, the proportion of children who received hospital eye services and required hospital admission was low (less than 10%) and with the fact that the total cost of ophthalmic surgery and inpatient eye services was less than that of ophthalmology outpatient eye services 15 ) .…”
Section: Discussionsupporting
confidence: 71%
“…A review of the published literature was carried out to explore current challenges in vision services for children and uptake of referrals and treatments. However, most of the literature reported findings from non-UK settings, and the few publications related to childhood vision care in the UK did not explore barriers to service uptake and treatment compliance ( Alexander et al 2009 ; Little & Saunders 2015 ; Bruce & Outhwaite 2013 ; Solebo et al 2013 ; Solebo et al 2015 ; Toufeeq & Oram 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that visual acuity measurements are the single most important factor for assessing the global visual performance of a child; 4,16 however, when visual acuity testing alone is performed with a sensitivity of 90 per cent, the specificity is only 50 per cent, 17 resulting in significant numbers of false positive results. As a result, the cost‐effectiveness of children's vision screening programs has been questioned in recent years 18,19 …”
mentioning
confidence: 99%